Hubungan Kejadian Katarak dengan Diabetes Melitus di Puskesmas Tanjung Harapan, Marga Tiga, Lampung Timur - Dwi Budi Santoso; Ferry Doringin; Murni Marlina Simarmata; Karla Sasia (Jurnal Mata Optik, 2022)
This study aims to determine the relationship between the incidence of cataracts and diabetes mellitus in patients at the Tanjung Harapan Health Center, Marga Tiga District, East Lampung Regency. The population in this study were outpatients for the period January - May 2021 using a case-control design with 38 subjects divided into 19 case groups (cataract patients) and 19 control groups (patients without cataracts). History of diabetes mellitus data seen from the patient's medical record and processed using the chi square test with a significance level of p <0.05. Analysis of hypothesis testing using SPSS version 21, the results of this study the asymp sig value of 0.020, which is <0.05, which means Ho is rejected, this proves that there is a significant relationship between the incidence of cataracts and Diabetes Mellitus. This data deserve to be tested with Chi Square because there is no Expected value less than 5